PENGARUH PENERAPAN MODEL DISCOVERY LEARNING BERBASIS MULTIPLE INTELLIGENCES TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA - Tiya Fathonah; Satya Santika; Ebih Abdul Rachim Arhasy (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2019)
This study aims to determine the effect of the application of Multiple Intelligences based Discovery Learning on students mathematical understanding ability and to find out the interest in learning mathematics of students after applying Multiple Intelligences based Discovery Learning. This study uses an experimental method with population of 312 eighth grade students of SMP Negeri 13 Tasikmalaya in the academic year 2018/2019. The sample is determined by cluster random sampling. 32 students from VIII-I class was chosen as the experimental class whose learning applied the Multiple Intelligences based Discovery Learning, while the VIII-H class which numbered 31 students was chosen as the control class whose learning applied the Discovery Learning model. The collection of research data is determined through a single test of mathematical understanding ability in the form of a description (posttest). The instrument of this study consisted of test questions of mathematical comprehension ability and students interest in learning mathematics. The data analysis technique uses the two average difference test. The results showed that there was an effect of the application of Multiple Intelligences based Discovery Learning models to the students 'mathematical understanding ability with students interest in mathematics learning in the high category.